Work ethics profile of vocational college students in Indonesia - Yohana Ika Harnita Sari; Endang Soelistiyowati; Erlin Estiana Yuanti (Jurnal Pendidikan Vokasi, 2020)
This study aims at describing the work ethics profile of Vocational College Students in Indonesia. Work ethics is an important indicator of human resources quality, and also an element of employability skills, that must be owned by students of Vocational College as working-age population. There are four main dimensions in work ethics: commitment, integrity, professional attitudes, and hard work. It is descriptive research on self-evaluation survey. It uses a Likert scale with five response options, ranging from 1 (never) to 5 (always). The respondents were determined using cluster sampling and convenience sampling. They are from four vocational colleges based on the three regions in Indonesia: College A (representing Western Indonesia colleges), College B and C (from Middle Indonesia), and College D (in Eastern Indonesia). This geographical perspective is used to get a profile of Vocational College students' work ethics regionally and nationally. The study concludes that there is no major difference among the self-evaluation results of work ethics in Western Indonesia, Middle Indonesia, and Eastern Indonesia (the mean scores of the four dimensions in four colleges range from 3.89 to 4.54). The study concludes that integrity is in the highest rank among other dimensions. The one that takes place in the second position is commitment, except the one in College C. It is consecutively followed by being professional (except College C since its being professional is in the second place). The last is hard work. This profile signals positive support towards the demographic dividend for the development of the country.